Pelatihan Upaya Pencegahan Diabetes Melitus Pada Lansia Di RW 02 Kelurahan Kedungdoro Surabaya - Rasemi Widayanti, Marcellina; Purnama, Ni Luh Agustini Purnama; Yuliati, Ignata (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Problems with the elderly in RW 02 Kedungdoro Village Surabaya, out of 256 elderly, 35 elderly (13.7%) suffer from diabetes mellitus. Most of the elderly have never checked their blood sugar levels, rarely do sports activities and have a habit of eating foods that contain more carbohydrates. The purpose of this community service is to provide training on how to prevent Diabetes Mellitus for the elderly in RW 02, Kedungdoro Village, Tegalsari District. The target of the activity is the elderly in RW 02, Kedungdoro Village, Tegalsari District, Surabaya, totaling 65 people. The activity was held on November 27 2022. Activities included health education about DM, practicing DM exercises, and monitoring blood sugar levels. This community service activity can be carried out properly. The elderly were very enthusiastic about participating in the activity. Based on the results of the pretest and posttest evaluations, there was an increase in knowledge about DM. The results of random blood sugar levels averaged 131.7 mg/dl. There were 6 elderly people whose random blood sugar levels were >200 mg/dl. Elderly people with high blood sugar levels feel grateful because they know their condition immediately and will carry out further examinations at the Puskesmas. This community service activity needs to be carried out on an ongoing basis with the DM exercise program and monitoring blood sugar levels through the Elderly Posyandu activity